Effect of Aged and Fermented Garlic Extracts as Natural Antioxidants on Lipid Oxidation in Pork Patties - Lee, Hyun-Jin (Food Sci Anim Resour, 2019)
The aim of this study was to investigate the natural antioxidant activity of raw garlic (RG), aged black garlic (AG), and garlic fermented with Bacillus subtilis (FG) extracts on pork patty lipid oxidation throughout refrigerated storage. The total polyphenol, total flavonoid content, 1,1-diphenyl-2-picrylhydrazyl (DPPH) and 2,2’-azino-bis-3-ethylbenzothiazoline-6-sulfonic acid (ABTS) radical scavenging activity of three different types of garlic extracts were measured. The total phenolic and flavonoid content of AG was significantly higher than that of FG and RG; FG also showed a significantly higher total phenolic content than that of RG (p<0.05). The DPPH and ABTS radical scavenging activity of AG and FG was significantly higher than that of RG and that of AG was significantly higher than that of FG (p<0.05). To investigate the effect of processed garlic extracts on pork patty lipid oxidation, freeze-dried extracts of RG, FG, and AG were added to the patties at levels of 0.5% (w/w). Patties containing 0.01% (w/w) ascorbic acid (AA) and patties without treatment (CON) were compared with patties containing garlic extracts. The pH value, 2-thiobarbituric acid reactive substances value, and volatile basic nitrogen value of pork patties containing AG and FG extracts were significantly decreased compared to the other groups (CON, AA, and RG; p<0.05). Taken together, these results suggest that AG and FG extracts possess strong antioxidative activity and can serve as natural antioxidative additives to prevent pork patty lipid oxidation.